Pengaruh Harga, Kualitas Produk Dan Kualitas Pelayanan Terhadap Volume Penjualan Produk Jasa Bordir Pada Cv. Aditama Di Kota Surabaya - Mahrusul Faizin; Achmad Daengs GS; Mahjudin Mahjudin; Diana Zuhro; Tjandra Wasesa (Jurnal Mahasiswa Manajemen dan Akuntansi, 2023)
This study analyzes the effect of price, product quality and service quality to increase sales volume embroidery services Aditama CV of Surabaya. Data were obtained from questionnaires and direct observation in the field. Data were analyzed using multiple linear regression. The finding’s show that the simultaneous price, product quality and service quality affect the volume of sales. This means that the price, product quality and service quality of each has and effect on the sale of embroidery services Aditama CV of Surabaya. Partially price variables have a dominant influence on the sales volume, which indicates that at an affordable price will increase the company's sales volume.